The golden braid ebook - Dickerson, Melanie (Hagenheim, 2015)
From New York Times bestselling author comes The Golden Braid, a Rapunzel retelling that proves the one who needs rescuing isn't always the one in the tower. Rapunzel can throw a knife better than any man. She paints beautiful flowering vines on the walls of her plaster houses. She sings so sweetly she can coax even a beast to sleep. But there are two things she is afraid her mother might never allow her to do: learn to read and marry. Fiercely devoted to Rapunzel, her mother is suspicious of every man who so much as looks at her daughter and warns her that no man can be trusted. After a young village farmer asks for Rapunzel's hand in marriage, Mother decides to move them once again—this time, to the large city of Hagenheim. The journey proves treacherous, and after being rescued by a knight—Sir Gerek—Rapunzel in turn rescues him farther down the road. As a result, Sir Gerek agrees to repay his debt to Rapunzel by teaching her to read. Could there be more to this knight than his arrogance and desire to marry for riches and position? As Rapunzel acclimates to life in a new city, she uncovers a mystery that will forever change her life. In this Rapunzel story unlike any other, a world of secrets and treachery is about to be revealed after seventeen years of lies. How will Rapunzel finally take control of her own destiny? And who will prove faithful to a lowly peasant girl with no one to turn to? "The Golden Braid is a delightful, page-turning retelling of the story of Rapunzel. Dickerson brings this familiar fairy tale to life with a fresh and unique plot that is full of complex characters, a sweet romance, and danger at every turn. Rapunzel's search to understand her place in the medieval world is a timeless identity struggle that modern readers will relate to. Her growing courage and faith are inspirational and will have readers cheering her on and sad to see the story come to an end." —Jody Hedlund, bestselling author of An Uncertain Choice